Особенности усвоения материала тренинга его участниками в зависимости от содержания тренинговой программы - Trus', А.; Lepeshinskiy, Николай (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The results of how effectively the participants learn the materials of communication and management training are presented in this article. The research was carried out in a form of the natural experiment. In the experiment such factors as professional competence and personal characteristics of the trainer and content of training program were controlled. It was discovered that the participants learned the materials of communication and management training differently. The higher the initial level of competence of the training participants the more effective is their learning of the training material. This is demonstrated in a level of communicative competence of the participants. At the same time the authors believe that personal characteristics of training participants play a significant role for successful learning of the communication and management training materials. The received results were implemented during development of «Effective Communication Technologies» course for students of the Command Faculty of the Institute for Command Engineers of the Ministry for Emergency Situations of the Republic of Belarus.